Coronavirus Pandemic’s Impact On Aquaponics Farmers: With Reference To Palakkad District - et. al., Ashwin Anand, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The COVID-19 pandemic is exerting a perilous effect on human life. The stringent restrictions imposed by the Government of India as part of this crisis resulted in an adverse effect on the economic bar graph of the country. The Aquaponics sector is one of the adversely affected sectors. Various factors such as lockdown, social distancing policies, forbidding restaurants to dine, interstate movement restrictions, cancellation of domestic and international flights have resulted in an unpropitious effect on Aquaponics farmers in Kerala. This research paper deals with the Coronavirus pandemic’s Impact on Aquaponics farmers in Kerala with special reference to the Palakkad district. The study is carried with the help of data collected from authorized Aquaponics farm units in Palakkad in Kerala. The survey is carried out through Google form. The collected samples were analyzed to understand the change in different constraints before and during the Coronavirus Pandemic.